Génération Crivelli - Thomas Golsenne (Images Re-Vues)
Studying Carlo Crivelli’s painting and carrier focusing on kinship appears full of perspectives. Starting from the interpretation formulated by Deleuze and Guattari about alliance as a form of creation, I try to analyse how Crivelli has actually elaborated his style through affinity or heterogenesis. But Crivelli has himself aroused a « family », the crivelleschi : these painters who imitated his style during around thirty years. In order to understand this phenomenon, we need another model: religious imitation, « hagiographic kinship » or « holy tribe ».